Analisis New Social Movement Terhadap Gerakan Sambatan Jogja (SONJO) Dalam Mengurangi Risiko dan Laju Paparan Kasus Covid-19 di Daerah Istimewa Yogyakarta - Perdana, Vicky Alfitra; David Efendi (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2023)
This study aims to identify sonjo movements in taking a role to help reduce the risk of the spread of Covid-19 in communities within the scope of Special Region of Yogyakarta Province. The research method used is qualitative with a case study approach and research also uses Civil Society theory and New Social Movement theory. The results of this study can be known sonjo made efforts in reducing the risk and countermeasures of Covid-19 by carrying out a program, namely Jimpitan Vaccination and encouraging the creation of village shelters driven by each area spread in Special Region of Yogyakarta Province by relying on the concept of mutual cooperation as a whole. However, in its implementation it looks not fully evenly distributed in this DIY Province area, there is still more movement in the Bantul Regency area. Even so, it is necessary for more vigorous efforts with more intensive socialization and assistance to each region so that the acceleration of the Covid-19 Pandemic response can be even better. The conclusion of this study is that the efforts made by SONJO are in accordance with the will of the situation in the field, but it still needs to be pursued more widely which covers the DIY region completely.